How did intellectuals conquer fashion? Nineteenth-century discourses (ModaPalavra e-periódico, 2019)
In this paper argue that the notion of "fashion" and his rhetoric, obtained a conceptual form similar to the one of "intellectual": two concepts flow into a back and forth between good and evil; the banal or the not superficial; among the ideologization, politicization and the de-ideologization or disappearance of their sense historical, political and cultural. Thus, work on a dualism (intellectuals -fashion) as related by a question mark, will allow us to understand what role meets an intellectual, and arguments casts when this is fashion.In addition, we intend to demonstrate that "sexes differences" are permanently linked with the subject in question. Therefore,we want to expose how the 'fashion' concept has been politicized during the period in which thinks "progress", modernization or modern (19th-century and early 20th), both in Europe and in the Río de la Plata (current Republic Argentina).
Keywords: intelligentsia; 19th century; fashion